The Efficacy of Simultaneous Injection of Dexamethasone Implant and Ranibizumab Into Vitreous Cavity on Macular Edema Secondary to Central Retinal Vein Occlusion - Du, Xing; Sheng, Yanjuan; Shi, Yeqiang; Du, Min; Guo, Yuanyuan; Li, Shanshan (Frontiers in Pharmacology, 2022)
The purpose of this study was to determine the safety and effectiveness of simultaneous vitreous injection of dexamethasone implant and ranibizumab on macular edema secondary to central retinal vein occlusion (CRVO). We conducted a 6-month retrospective self-control study. Twenty-five patients diagnosed with macular edema secondary to CRVO were enrolled in this study. The patients received intravitreal injection of dexamethasone implant and ranibizumab. The changes in best corrected visual acuity (BCVA), central retinal thickness (CRT) and interocular pressure (IOP) before and at 2w, 1m, 2m, 3m, 4m, 5m, 6m after injection were recorded and compared. The adverse reactions in eyes and whole body were observed. The BCVA of all patients at 2w (61.8±5.42), 1m (68.68±5.23), 2m (70.8±5.8), 3m (68.44±5.61), 4m (65.76±5.76), 5m (67.08±5.57), and 6m (70.12±5.46) after surgery were significantly higher than that before surgery (52.2±5.06,P<0.01), and CRT of all patients at 2w (393.36±52.66um), 1m (334.52±32.95um), 2m (298.800±29.97um), 3m (309.080±28.78um), 4m (345.48±39.81um), 5m (349.080±29.88um), and 6m (309.76±30.41um) after surgery were significantly reduced than that before surgery (583.76±121.09um, P<0.01). Macular edema recurred in an average of 4.44±0.51 months after treatment, and those patients received combined treatment again. During follow-up, the most common adverse reactions were subconjunctival hemorrhage and increased intraocular pressure, with the incidence of 22%(11/50) and 18%(9/50) respectively. In all cases, the increased intraocular pressure could be controlled by a single intraocular pressure reducing drug. No patient needed to receive anti-glaucoma surgery. The overall incidence of lens opacity was 4%(2/50). After the first injection, no case showed lens opacity. After re-injection, 2 patients (2 eyes) (8%) developed lens opacity. None of the patients showed serious ocular adverse reactions or systemic complications such as vitreous hemorrhage, retinal detachment, endophthalmitis, uveitis or ocular toxicity. The simultaneous vitreous injection of dexamethasone implant and ranibizumab can significantly improve the visual acuity and anatomical prognosis in macular edema secondary to central retinal vein occlusion (CRVO-ME) patients, exhibiting good safety and effectiveness.